William Pollock Fraser (1867-1943) : Canadian pioneer plant pathologist-mycologist - Estey, R.H. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1992)
William P. Fraser, the first Canadian-born plant pathologist-mycologist to be internationally recognized as such, began as an amateur collector of fungi, with emphasis on the plant rusts, while teaching school in his home province, Nova Scotia. He then became a widely acclaimed authority on the rusts and a professional plant pathologist-mycologist. He taught plant pathology and mycology, first at McGill University and then, after an interval as head of the first plant pathology laboratory in Western Canada, at the University of Saskatchewan. Fraser was a Canadian pioneer in research on physiological races of wheat rust; in the culture of heteroecious rust fungi, in forest pathology, and in the study of root and smut diseases of grasses in Western Canada.